Analisis Lama Penggunaan Komputer Pada Mahasiswa Universitas ABC Dengan Metode Algoritma C4.5 - Wida Pesah Sucihermayanti; Daniel Tunggono Saputro; Grace Gabriella Herald; Yeremia Chris Saragi (Jurnal Informa : Jurnal Penelitian dan Pengabdian Masyarakat, 2021)
Nowadays computers are a very important technology and widely used, almost in all sectors of the field, one of which is in the field of education. In ABC University we know that every student must have or even used a computer often. For this reason, the authors make research on the duration of computer use in students and anything that can affect the duration of students in using computers. Using the C4.5 Algorithm the author created a decision tree where the decision tree is made from datasets that have been collected from several students who filled out the questioner. Then the dataset calculation results will provide a rule or scheme where students can be said to have used a computer for a long time or not. For example, students in the last semester or semester 8 can be said to be using a computer for a long time.